Management of a Large Internal Resorption Lesion with Metal Reinforced Glass Ionomer Cement - Gurdeep Singh Gill; Atool Chandra Bhuyan; Suraj Arora; Kunal Sethi; Rajwinder Kaur; Tarun Kalra (Hindawi Limited, 2014)
Mineral trioxide aggregate is the mainstay of treatment of large internal resorption defects. But its cost may be a deterrent to its use in some patients. The present case report describes the successful endodontic management of an extensive internal resorptive lesion in a mandibular molar with metal reinforced glass ionomer cement.